Effect of electrolyte addition and type of solvents used on the quality of nanofiber scaffold - Khoo, Ying Siew (2017)
Nanofiber-based scaffolding systems are now can mimic the natural extracellular matrix (ECM) of desired tissue to be regenerated and can replace organ transplantation in future. The objective of this study is to determine effect of electrolyte addition and type of solvents used on the quality of nanofibers scaffold. Besides that, the research will proceed to the fabrication of drug embedded nanofibers mat to detect the presence of the drug dissolved in nanofibers mat. In this study, needleless electrospinning technique is applied by using the advanced equipment called Elmarco Nanospider™ to fabricate nanofibers scaffold. Meanwhile, polyethylene oxide (PEO) and polycaprolactone (PCL) polymers were used in this studied. PEO solution was undergoes surface morphology studied by determine the effect of concentration and effect of additional electrolyte on the quality of nanofibers. While PCL polymer was used in study the effect of using different kind of solvents on the quality of nanofibers and also fabrication of drug embedded nanofibers. From the result, PEO 2 obtained a low diameter range of 100 nm to 125 mm and no bead formed compare to PEO 1. While for PEO 3 that contained electrolyte composition, it obtained a 75 nm to 100 nm diameter compare to PEO 2. For PCL that dissolve with DCM, nanofibers obtained were in range of 100nm to 300nm and smooth compare to PCL mixed with DMF and CHCl₃. However, since PEO cannot dissolve completely with curcumin and titanocene drug, PCL is used in this drug fabrication. PCL that mixed with curcmin obtained a higher existence with 18.79% in the nanofibers mat compare to drug titanocene with only 5.586%. In this study, SEM, Image J, FTIR and EDX were used in characterization study of nanofibers. As a conclusion, electrolyte addition can increase the conductivity and DCM solution with low boiling point can eject the solution more easily to the collector.